DAYA TARIK WISATA PADA PERMAINAN RAKYAT PANGKAK GASING DI KABUPATEN NATUNA - Fitrimeutia, Chindi; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Located at the northern tip of Indonesia, Natuna Regency not only has a lot of natural potential, but many interesting cultural attractions, and also a variety of culinary delights. One form of cultural tourism resource in Natuna Regency is the traditional game Pangkak Gasing. This research aims to reveal the folk game Pangkak Gasing as a potential tourist attraction to bring tourists to Natuna Regency. By taking a qualitative approach by collecting data through interviews with five informants and direct observation at the destination. Then the results of the interview were analyzed using Grounded Theory analysis techniques. The research results show that the main attraction of Pangkak Gasing folk games tourism is cultural heritage and cultural tourism. Apart from that, cultural heritage and cultural tourism also have several groupings to explain the tourist attraction of the folk game Pangkak Gasing. Keywords: Tourist Attraction, Folk Games, Culture.